MENINGKATKAN HASIL BELAJAR SISWA DENGAN MELALUI MEDIA VISUAL PADA PEMBELAJARAN TEMATIK (TEMA 1 SUB TEMA 2) DI KELAS I SD NEGERI 04 KAJAI PARIAMAN - Pindawati Pindawati (Ensiklopedia Education Review, 2020)
The low student learning outcomes in Thematic Learning Theme 1, Sub Theme 2 are caused by several factors, including student activities that are lacking in media that does not exist and the lack of source books for students so that it affects the student's involvement in the learning carried out. In this case the researcher as a class conducted a research entitled